Predictors of renal outcome in ANCA-associated glomerulonephritis - Ljubičić, Bojana; Azaševac, Tijana; Popović, Milica; Živković, Siniša; Božić, Dušan; Ćelić, Dejan (Vojnosanitetski pregled, 2021)
Backgraund/Aim. Primary anti-neutrophil cytoplasmatic antibody (ANCA)-associated vasculitis are chronic multisystemic autoimmune diseases which include microscopic polyangitis (MPA), granulomatosis with polyangitis (WG), eosinophilic granulomatosis with polyangitis (EPGA; churg-strauss syndrome – CSS), and also a localized forms of illness. In our research, we studied clinical and serological parameters in patients, in order to find out which of them would be the best predictor of renal outcome in ANCA-associated vasculitis. Methods. Data from 42 patients with diagnose of MPA (9), WG (17), EPGA (0), CSS (0), and also idiopathic rapidly progressive glomerulonephritis (ROEB) without immune deposits (renal-limited vasculitis – 16) were analyzed. Cockroft formula was used for calculating the glomerular filtration in the moment of presenting the illness, and also after five year follow-up period. Other factors that were analyzed are: gender, age, type of ANCA antibodies, type of infections, stage of chronic kidney disease, need for heamodialysis and mortality. Results. Of a total of 42 patients, 17 (40.48%) were male. The average age of the patients at the time of diagnosis was 57.8 (± 10.44) years. Seventeen patients (40.48%) had a diagnosis of WG, 9 (21.43%) MPA, and 16 (38.09%) iRPGN. The presence of positive anti-proteinase (anti-PR3) antibodies was confirmed in 18 patients, and anti-MPO antibodies in 17 patients. Three patients had both subtypes of ANCA antibodies (anti-PR3 and anti-MPO). Initially, 12 patients required heamodialysis treatment. Twenty nine patients had a complete and 13 patients had partial remission. Out of the total number of patients, 8 patients (19.04%) developed the terminal renal failure stage, and ended up on a chronic dialysis program. During a five-year follow-up period, 12 patients (28.57%) resulted in death. The age of the patient proved to be statistically significant predictor of glomerular filtration rate (GFR) at the moment of presentation of the disease (p = 0.011). GFR t = 0 was statistically significant (p = 0.000) for the evaluation of kidney function outcomes in ANCA-associated glomerulonephritis. Conclusion. Kidney function in the moment of illness presentation, determined by GFR t = 0, is the most important significant factor for predicting renal outcome in ANCA-associated vasculitis, and also the mortality in these patients.